Penyuluhan Edukasi Menjaga Kebugaran pada Kelompok Lansia Prolanis di Puskesmas Pembantu Banjarejo - Wiwit Primaningati; Arys Hasta Baruna; Tarmiah Tarmiah (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Aging is a process where person experiences with a lot of physiological decline and is susceptible to disease. there are several factors that influence fitness in elderly such a physical activity, quality of sleep and nutritional intake. Exercise, adequate sleep patterns and quality and nutrition intake have a positive impact on maintaining fitness in elderly. Method : method was used in this counseling of health promotion using poster media regarding fitness for elderly with a total of 26 participants. Result and conclusion : the counseling session went well and the participants can understand about the materi, it is hoped this education can be applied in their daily living.